Cellular neural network based deformation simulation with haptic force feedback - Zhong, Yongmin; Shirinzadeh, B.; Alici, G.; Smith, J. (IEEE, 2006)
This paper presents a new methodology fordeformable object modelling by drawing an analogybetween cellular neural network (CNN) and elasticdeformation. The potential energy stored in an elasticbody as a result of a deformation caused by anexternal force is propagated among mass points by thenon-linear CNN activity. An improved CNN model isdeveloped for propagating the energy generated bythe external force on the object surface in the naturalmanner of Poisson equation. The proposedmethodology models non-linear materials with nonlinearCNN rather than geometric non-linearity in themost existing deformation methods. It can not onlydeal with large-range deformations, but it can alsoaccommodate isotropic, anisotropic andinhomogeneous materials by simply modifyingconstitutive constants.